Re-imagining Education Policy and Practice in the Digital Era - Altass, Patricia; Wiebe, Sean (Journal of the Canadian Association for Curriculum Studies, 2017)
New digital technologies are changing the nature and contexts of work in Canada. It is essential that education policy and practice acknowledge and respond to these changes. The impacts and implications of new and emerging technologies for work can be summarized within two paradigms: technology is replacing work through automation and digital Taylorism; and technology is changing communication, collaboration and knowledge creation. Derived from a SSHRC Knowledge Synthesis report, this article explores how nurturing uniquely human abilities by employing a threshold concept approach will help create education policy and practice that can better prepare students for the realities of the evolving knowledge-based creative economy. Highlighting the complexity and transdisciplinary nature of knowledge, The New Literacies Threshold Concepts in English Language Arts are presented as a curriculum heuristic that is well-suited to developing uniquely human abilities.